Synthesis of Catalyst from Agricultural Wastes for Palm Oil Conversion into Biodiesel - Mohd Fisol, Aiman Naqib; Mohd Sithik, Muhammad Fikri; Wan Ahmad Razman, Wan Adam Mukhriz; Mohd Zuhan, Mohd Khairul Nizam (Multidisciplinary Applied Research and Innovation, 2026)
The increasing demand for sustainable energy has encouraged the search for cost-effective and environmentally friendly catalysts for biodiesel production. Homogeneous catalysts are commonly used in transesterification, but their corrosive nature and difficulty in separation reduce their practicality. This study investigates the use of banana, durian, and mango peels as heterogeneous catalysts derived from agricultural waste. These peels were dried and calcined at temperatures ranging from 400 °C to 600 °C to produce ash catalysts, which were then tested for biodiesel production from palm oil. SEM-EDX analyses revealed that banana peel ash had the highest potassium content at 52.24 wt.%, followed by durian and mango peels. FTIR analysis of the biodiesel confirmed strong ester peaks at 1740 cm⁻¹, indicating successful methyl ester formation. Among the three catalysts, banana peel ash demonstrated the most effective catalytic activity, yielding biodiesel with a yield above 90%. This study demonstrates the potential of fruit peel waste as a sustainable source of a catalyst for biodiesel production.